Intra-domain phage display (ID-PhD) of peptides and protein mini-domains censored from canonical pIII phage display - Tjhung, Katrina F.; Deiss, Frédérique; Tran, Jessica; Chou, Ying; Derda, Ratmir (Frontiers in Microbiology, 2015)
In this paper, we describe multivalent display of peptide and protein sequences typically censored from traditional N-terminal display on protein pIII of filamentous bacteriophage M13. Using site-directed mutagenesis of commercially available M13KE phage cloning vector, we introduced sites that permit efficient cloning using restriction enzymes between domains N1 and N2 of the pIII protein. As infectivity of phage is directly linked to the integrity of the connection between N1 and N2 domains, intra-domain phage display (ID-PhD) allows for simple quality control of the display and the natural variations in the displayed sequences. Additionally, direct linkage to phage propagation allows efficient monitoring of sequence cleavage, providing a convenient system for selection and evolution of protease-susceptible or protease-resistant sequences. As an example of the benefits of such an ID-PhD system, we displayed a charged FLAG sequence, which is known to be post-translationally excised from pIII when displayed on the N-terminus. ID-PhD of FLAG exhibited sub-nanomolar apparent Kd suggesting multivalent nature of the display. A TEV-protease recognition sequence (TEVrs) co-expressed in tandem with FLAG, allowed us to demonstrate that 99.9997% of the phage displayed the FLAG-TEVrs tandem and can be recognized and cleaved by TEV-protease. The residual 0.0003% consisted of phage clones that have excised the insert from their genome. ID-PhD is also amenable to display of protein mini-domains, such as the 33-residue minimized Z-domain of protein A. We show that it is thus possible to use ID-PhD for multivalent display and selection of mini-domain proteins (Affibodies, scFv, etc.).